Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts prepared with different precipitating agents - Tangale, Nilesh P.; Niphadkar, Prashant S.; Deshpande, Shilpa S.; Joshi, Praphulla N. (Applied Catalysis A-General, 2013)
Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts (molar Cu:Al = 1:1) prepared by reduction of mixed oxide precursors synthesized using different precipitating agents viz, potassium carbonate, tetraalkyl ammonium hydroxides (TAAOHs) and urea was investigated. In order to assess the efficacy of TAAOH further, the chain length of tetraalkyl ammonium cations was also varied and the resulted catalysts were evaluated for their catalytic performance. The catalysts were characterized by powder X-ray diffraction, low temperature nitrogen adsorption, temperature programmed desorption of ammonia and UV-visible diffuse reflectance spectroscopy. The dependence of the catalyst performance on the precipitating agent employed during its synthesis has been clearly demonstrated. The use of TAAOH as precipitating agent led to the formation of a catalyst with better catalytic activity than those prepared using potassium carbonate and urea. Further improvement in the catalytic performance was observed when TAAOH with longer alkyl chain ammonium cation was used. The optimum catalyst prepared by reduction of mixed oxide precursor synthesized using tetrapropyl ammonium hydroxide as precipitating agent, showed highest cyclohexanol conversion (81.5%) and cyclohexanone selectivity (79.6%) at 250 degrees C on account of higher Cu+/Cu-0 ratio, well dispersed copper, higher surface area and lower total acidity with higher contribution of sites with moderate strength. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Characterization; Cu/Al2O3; Cyclohexanol dehydrogenation; Precipitating agent; Tetraalkyl ammonium hydroxide

Enhanced mineralization of gaseous organic pollutant by photo-oxidation using Au-Doped TiO2/MCM-41 - Tangale, Nilesh P.; Belhekar, Anuja A.; Kale, Kishor B.; Awate, Shobhana V. (Water Air and Soil Pollution, 2014)
The synthesis, characterization, and photocatalytic evaluation of titania-loaded MCM-41 with and without Au doping are reported in the present study. The samples were characterized by powder XRD, TEM, low temperature N-2 adsorption/desorption, UV-Vis, and FTIR. UV-induced vapor-phase photo-oxidation of acetone was used as a probe reaction to study the role of Au in mineralization of volatile organic compounds (VOCs), viz. acetone at different concentrations. The doping of Au in titania-loaded MCM-41 resulted in the decrease of BET surface area, total pore volume, and average pore size. UV-Vis diffuse reflectance spectra of Au-doped titania-loaded MCM-41 showed the red shift in their absorption bands compared to titania-loaded MCM-41. The activity of mineralization of acetone by photocatalysis for 2 % Au-doped titania-loaded MCM-41 was found to be similar to 1.6 times higher than titania-loaded MCM-41. The presence of cocatalytic nanosized gold might be responsible for their enhanced activity on account of the delayed recombination of electron/hole pair. Although, almost complete mineralization of acetone was observed irrespective of the initial concentration of acetone in air (up to 3.72 mol%) by all the catalysts, 2 wt.% Au-doped titania-loaded MCM-41 has shown the most enhanced activity.
Keywords: Acetone; Doping; Gold; Mineralization of VOCs; Photo-oxidation; TiO2/MCM-41

Hierarchical K/LTL zeolites: synthesis by alkali treatment, characterization and catalytic performance in knoevenagel condensation reaction - Tangale, Nilesh P.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N. (Journal of Industrial and Engineering Chemistry, 2016)
The hierarchical K/LTL zeolites prepared by post-synthesis modification with aqueous 1.5 M KOH solution by varying alkali volume to K/LTL zeolite (10-70 ml/g) ratios, were examined in Knoevenagel condensation. The physico-chemical properties of the catalysts were thoroughly evaluated by PXRD, ICP, CO2-TPD, XPS, N-2 adsorption/desorption and Si-29 and Al-22 MAS-NMR. Among all the samples, hierarchical K/LTL prepared by treating K/LTL with 50 ml aqueous 1.5 M KOH solution per gram of K/LTL displayed about 1.5 fold higher catalytic activity as compared to parent K/LTL, presumably because of combined effect of enhanced basicity and molecular diffusion through pore channels. (C)2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Basicity; Hierarchical zeolite; K/LTL; Knoevenagel condensation; Micro-mesoporous composite

KLTL-MCM-41 micro-mesoporous composite as a solid base for the hydrogenation of sugars - Tangale, Nilesh P.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
An approach to the synthesis of KLTL-MCM-41 micro-mesoporous composites of varying SiO2/Al2O3 molar ratio (20-8) was designed by following green technology. The synthesis was based on the recycling of waste mother liquor containing preformed KLTL zeolite crystals and unutilized reagents. The micro-mesoporous composites consist of KLTL zeolite crystals preformed through hydrothermal treatment in the first step. In the second step, the siliceous mother liquor was transformed into mesoporous MCM-41. The physico-chemical properties of the KLTL-MCM-41 micro-mesoporous composites were determined by PXRD, ICP-OES, FTIR, CO2-TPD, Al-27 MAS-NMR, TEM-EDX, HRTEM, and N-2 adsorption-desorption measurements. The mesopores properties of the KLTL-MCM-41 composites depended on the SiO2/Al2O3 molar ratio. The characterization results led to the following conclusions with decreasing SiO2/Al2O3 molar ratio: 1) decreasing order of the mesophase, 2) decreasing wall thickness of the mesopores, and 3) decreasing BET surface area and pore volume. Al-27 MAS-NMR spectra showed that only tetrahedrally coordinated aluminium was contained in zeolite KLTL. Moreover, the total amount and the strength of the basic sites of the KLTL-MCM-41 micro-mesoporous composites owing to the exchangeable potassium content (Al/K ratio approximate to 1) decreased in the order: 8 MMC > 10 MMC > 15 MMC > 20 MMC. The catalytic activity of the synthesized micro-mesoporous samples as a solid base was tested for the hydrogenation of xylose to sugar alcohols